Administrative reform assistance and democracy promotion: exploring the democratic substance of the EU's public administration reform principles for the neighbourhood countries. Issue 4 (19th May 2018) - Muhhina, Kristina
ABSTRACT: International donors, particularly the European Union (EU), vehemently endorse institution-building and public administration reform (PAR) in their work on democracy support. Still, the linkages between externally sponsored reform and advancement of democratic governance in beneficiary countries constitute a blind spot in our understanding of democratization. This article contributes to examining this relationship by exploring the democratic substance of the EU's PAR portfolio for the neighbourhood countries. The aim of the article is to focus attention on the PA–democracy interface in the study of democracy promotion by elaborating a conceptual framework for exploring the nature of externally supported administrative reforms and the substantive content of democracy being advanced. By using the OECD/SIGMA's (Organization for Economic Co-operation and Development/Support for Improvement in Governance and Management) PAR framework for the European Neighbourhood Policy (ENP) countries as a case study, this article demonstrates how the EU's approach to programming PAR accommodates elements from several formats of democratic governance while the conceptualization of the democratic effects of the PAR principles remains vague. The article concludes by highlighting the need for closer examination of the potentials and limits of external PAR strategies in democracy support, and for attuning the EU's PAR design to its democratic implications.